2014
DOI: 10.1088/2041-8205/787/2/l29
|View full text |Cite
|
Sign up to set email alerts
|

Habitable Zones Around Main-Sequence Stars: Dependence on Planetary Mass

Abstract: The ongoing discoveries of extrasolar planets are unveiling a wide range of terrestrial mass (size) planets around their host stars. In this letter, we present estimates of habitable zones (HZs) around stars with stellar effective temperatures in the range 2600 K -7200 K, for planetary masses between 0.1 M ⊕ and 5 M ⊕ . Assuming H 2 O-(inner HZ) and CO 2 -(outer HZ) dominated atmospheres, and scaling the background N 2 atmospheric pressure with the radius of the planet, our results indicate that larger planets… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
804
6
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(850 citation statements)
references
References 45 publications
19
804
6
11
Order By: Relevance
“…This result highlights that systems with a Jovian with e 0.4 near the HZ seem unlikely to be able to host a rocky planet within the HZ. This Kopparapu et al (2014), while the orange region indicates the chaotic region as per the equations presented by Giuppone et al (2013). The size of each planet represents the mass ratio, µ = M planet /M , of the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result highlights that systems with a Jovian with e 0.4 near the HZ seem unlikely to be able to host a rocky planet within the HZ. This Kopparapu et al (2014), while the orange region indicates the chaotic region as per the equations presented by Giuppone et al (2013). The size of each planet represents the mass ratio, µ = M planet /M , of the system.…”
Section: Resultsmentioning
confidence: 99%
“…The CELESTA database calculates the HZs of nearby Sun-like stars, calculating the stellar properties needed to determine the HZs from Kopparapu et al (2014), and presents several possible HZ boundaries to choose from. As a large proportion of the exoplanet population is observed around non-Sun-like stars (e.g.…”
Section: Exoplanet Populationmentioning
confidence: 99%
“…We use here the common definition of a habitable climate that liquid water is stable at the surface (Kasting et al 1993). Important parameters influencing the habitability of a planet are its mass, its atmospheric composition and the intensity and the spectrum of the stellar flux it receives (Kasting et al 1993;Kopparapu et al 2014). Recently, it has been shown that furthermore the rotation period of a planet around its own axis influences its habitability .…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, this term is applied to individual star systems. Radiative transfer calculations of the atmospheric response of an Earthlike planet to insolation (Kasting, Whitmire & Reynolds, 1993;Kopparapu et al, 2013Kopparapu et al, , 2014 allow the identification of planetary orbits that permit surface liquid water. This is the principal definition of "the habitable zone", and we henceforth refer to it as the stellar habitable zone (SHZ).…”
Section: Introductionmentioning
confidence: 99%